Genetic diversity of Guava varieties (Psidium guajava L.) based on morphology and ISSR molecular markers - PHAN THI THU HIEN; LE THI TUYET CHAM; VU THI THUY HANG (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Hien PTT, Cham LTT, Hang VTT. 2024. Genetic diversity of Guava varieties (Psidium guajava L.) based on morphology and ISSR molecular markers. Biodiversitas 25: 1037-1045. Guava (Psidium guajava L.) is a fleshy-fruited representative belonging to the Myrtaceae family that has attracted attention due to its economic benefits. In this study, seventeen guava varieties in the Mekong Delta and Hanoi were collected and genetically validated by both morphology and DNA markers. The results revealed that fruit shape is a powerful indicator of guava discrimination. There are 12 out of 15 Inter Simple Sequence Repeats (ISSR) markers that show informative band patterns and 93 amplicons are generated with the size in length 200-2000 bp. The average polymorphic band and PIC value are 97.85% and 36%, respectively. Based on the dendrogram constructed by the Unweighted Pair Group Method using arithmetic Averages (UPGMA) method, samples were grouped into two main groups and the similarity level ranged from 55-98%. Group 2 contains Oi Tim (Purple guava), a special variety that showed high differences in terms of morphology and DNA profiles. Such information reflects the diversity of guava germplasm in Viet Nam, which is useful for conservation, and breeding strategies. The result revealed that 11 varieties expressed genetic diversity through both phenotypic traits and DNA profiles. Such information illustrates the genetic diversity among Psidium guajava, contributing to germplasm resources and plant breeding programs.